Nebulized glycosylated caffeic acid phenylether ester attenuation of environmental particulate-induced airway inflammation in horses - Rutledge, Jessica J.; Paegelow, Jillian; Ritchey, Jerry; Singh, Anuradha; Rizzi, Theresa; Murray, Cynthia; Gilliam, Lyndi; Crisman, Evan; Williams, Natasha J.; Holbrook, Todd C. (Frontiers in Veterinary Science, 2022)
The objective of this study was to determine the extent that nebulized glycosylated caffeic acid phenylether ester-4-O-alpha-D-glucopyranoside (G-CAPE) attenuates particulate-induced airway inflammation in healthy horses. Our hypothesis was that nebulization with G-CAPE would result in improved respiratory scores, higher arterial oxygen partial pressure, and less inflammatory airway infiltrates in horses with induced airway inflammation, compared with untreated controls. Five healthy adult horses were housed inside a climate controlled, closed barn on straw bedding and fed ad lib moldy grass hay for 16 days to induce airway inflammation. An experimental crossover study was performed in which animals were treated with 200 mg G-CAPE dissolved in 45 mL of 10% triethanolamine (G-CAPE group) or 45 mL of 10% triethanolamine (CONTROL group), and clinical respiratory scoring, arterial blood gases, and bronchoalveolar lavages (BALs) were collected at predetermined time points up to 24 h post nebulization. While the mean neutrophil percentage decreased in treated horses compared to controls (9.3 ± 2.0 and 16.9 ± 2.4, respectively) at 6 hours post treatment (t = 6 h), the difference did not achieve statistical significance (p = 0.1154). Blood gas analysis did not differ significantly between groups. There was a significant difference in the mean respiratory scores of G-CAPE-treated horses between baseline and at 1-h post treatment (from 3.2 ± 0.7 to 1.6 ± 0.7, p = 0.0013). This study demonstrates that a single nebulized dose of G-CAPE decreased clinical respiratory scores 1 h post administration and decreased BAL percentage of neutrophils 6 h post administration in horses with particulate induced airway inflammation. This compound shows promise as an anti-inflammatory and warrants further investigation.